2 - Interrogating Public Sphere and Popular Culture as Theoretical Concepts on their Value in African Studies - Willems, Wendy (Africa Development, 2021)
Concepts such as civil society and public sphere have been frequently used both as analytical tools and as normative concepts deemed essential to a wellfunctioning liberal democracy. Because of its theoretical roots in Western liberal thinking, scholars in African studies such as Comaroffs, Mamdani and Ekeh have vigorously debated the extent to which the concept of civil society is useful in explaining and interrogating developments in Africa. However, the concept of the public sphere has been subjected to less rigorous debate in the field of African studies. In media studies and political science, however, a number of scholars have problematised the normative connotations and idealistic assumptions of the Habermasian public sphere. This article argues that both the debate on civil society in African studies and the debate on public sphere in media studies and political science could inform a more critical discussion on the relevance of the concept of public sphere in African contexts. Secondly, the article contends that the concept of popular culture addresses some of the concerns brought up by critics of the concept of public sphere. It argues that popular culture is the public sphere of ordinary Africans, but we must be careful about how we define popular culture itself.